Product Market Competition and Economic Performance in New Zealand - Mourougane, Annabelle (OECD Economics Department Working Papers, 2005)
The paper examines the current state of competition in a number of sectors that are important for the economy. Because of the country's small size and isolation, the analysis focuses on barriers to entry, investment and external trade, rather than some standard indicators of competition stance. The competition law and institutions are generally well-conceived, although high-profile litigation about mergers and market-power problems hasstretched their capacities and until recently, diverted attention from enforcement against price fixing. Overall, markets appear to function well in New Zealand, but progress towards liberalisation seems recently to have lost momentum. In particular, improvement could be made in three main areas: in the energy sector, lifting current barriers to investment and developing forward markets are necessary to ensure the economy will be able to cope with long-term challenges; in telecommunications markets, concerns have been mounting regarding high prices and slow deployment of broadband; and in the public sector, there is scope for further use of private delivery for public services and reducing state ownership, especially in potentially competitive markets. Some adjustments to the regulatory framework and policies in a number of other sectors would also be beneficial. This Working Paper relates to the 2005 OECD Economic Survey of New Zealand (www.oecd.org/eco/surveys/nz)